2022
DOI: 10.1007/s00269-022-01199-1
|View full text |Cite
|
Sign up to set email alerts
|

On the crystal-chemistry of meyerhofferite, CaB3O3(OH)5·H2O

Abstract: The crystal structure and crystal chemistry of meyerhofferite, ideally CaB3O3(OH)5·H2O, was investigated by a multi-methodological approach based on titrimetric determination of boron, gravimetric determination of calcium, determination of fluorine by ion selective electrode, determination of water content by heating, other minor elements by inductively coupled plasma atomic emission spectroscopy, along with single-crystal synchrotron X-ray and neutron diffraction. The concentration of more than 50 chemical el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
(47 reference statements)
2
2
0
Order By: Relevance
“…The experimental findings about the complex and pervasive nature of the H-bonding scheme in inderborite confirm the previous results for other hydrous borates (e.g., Lotti et al 2018Lotti et al , 2019Gatta et al 2019Gatta et al , 2020Gatta et al , 2022aGatta et al , 2002b. We expect that a thermal, compressional or chemical perturbation of the H-bonding scheme would easily lead to a phase transition, or even to a decomposition of this mineral.…”
Section: Tablesupporting
confidence: 89%
See 3 more Smart Citations
“…The experimental findings about the complex and pervasive nature of the H-bonding scheme in inderborite confirm the previous results for other hydrous borates (e.g., Lotti et al 2018Lotti et al , 2019Gatta et al 2019Gatta et al , 2020Gatta et al , 2022aGatta et al , 2002b. We expect that a thermal, compressional or chemical perturbation of the H-bonding scheme would easily lead to a phase transition, or even to a decomposition of this mineral.…”
Section: Tablesupporting
confidence: 89%
“…), i.e., CaO 11.2(2) wt% and MgO 7.9(2) wt%. As commonly observed for hydrous borates (e.g., Gatta et al 2022b), even in this case a modest degeneration of the crystals was observed under the electron beam.…”
Section: Chemical Characterizationsupporting
confidence: 80%
See 2 more Smart Citations